MARKETING MIX ON TUAHTA FARM LIVESTOCK BUSINESS IN PAYA BUJOK SEULEUMAK VILLAGE, LANGSA BARO DISTRICT, LANGSA CITY - Puspita, Hilda; Gustiana, Cut; Basriwijaya, Kiagus Muhammad Zain (Syarif Hidayatullah State Islamic University Jakarta, 2024)
This study analyzed the marketing mix of the Tuahta Farm livestock business in Paya Bujok Seuleumak Village, Langsa Baro District, Langsa City. Observation, interviews, and direct questionnaires with respondents obtained primary data. In this study, the informant owned Tuahta Farm in Paya Bujok Seuleumak Village, Langsa Baro District, Langsa City. The sampling technique in this study uses the case study method. The data analysis used was descriptive qualitative. The results showed that: 1) The product mix for various products is less varied, for design is still the same as product design in general; 2) Price mix and payment methods are less diverse. 3) Promotion mix: Promotional activities have not gone well, so you should make a clear advertising strategy. 4) The distribution mix is already good compared to the product, price, and promotion mix.